2015
DOI: 10.4172/2378-5756.1000335
|View full text |Cite
|
Sign up to set email alerts
|

ICD-11 Trauma Questionnaires for PTSD and Complex PTSD: Validation among Civilians and Former Abducted Children in Northern Uganda

Abstract: Journal of Psychiatry AbstractObjectives: ICD-11 is expected to introduce a new diagnosis of C-PTSD, along with a revision of the current PTSD diagnosis. Are the suggested diagnostic tools for PTSD and C-PTSD valid in a developing country? Method:The tools have been tested on former abducted and regular civilians in northern Uganda (n=314), who have been influenced by the civil war that lasted for more than two decades. Results:The prevalence of either PTSD or C-PTSD was 36.6% and PTSD and C-PTSD was further f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(29 citation statements)
references
References 16 publications
0
29
0
Order By: Relevance
“…However, at the time of planning the current study, no instrument was yet available to assess the proposed ICD-11 criteria (Brewin et al, 2009; Maercker et al, 2013). We are aware that in the meantime an instrument assessing the proposed ICD-11 criteria was developed (Cloitre, Roberts, Bisson, & Brewin, 2015) that has been used in recent research (Dokkedahl, Oboke, Ovuga, & Elklit, 2015). However, this instrument has not been well enough established and validated up to now.…”
Section: Discussionmentioning
confidence: 99%
“…However, at the time of planning the current study, no instrument was yet available to assess the proposed ICD-11 criteria (Brewin et al, 2009; Maercker et al, 2013). We are aware that in the meantime an instrument assessing the proposed ICD-11 criteria was developed (Cloitre, Roberts, Bisson, & Brewin, 2015) that has been used in recent research (Dokkedahl, Oboke, Ovuga, & Elklit, 2015). However, this instrument has not been well enough established and validated up to now.…”
Section: Discussionmentioning
confidence: 99%
“…However, most of this research has been restricted to high-income countries (HICs), whereas significantly fewer studies have analysed samples from low- and middle-income countries (LMICs); e.g. Uganda (Dokkedahl, Ovuga, & Elklit, 2015 ; Murphy, Elklit, Dokkedahl, & Shevlin, 2016 , 2018 ); Angola (Rocha et al, 2019 ); Ghana, Kenya, and Nigeria (Ben-Ezra et al, 2020 ; Owczarek et al, 2020 ); Ukraine (McElroy et al, 2019 ; Shevlin et al, 2018 ); and Lebanon (Hyland et al, 2018 ; Vallières et al, 2018 ). Further research in LMICs is therefore necessary to determine whether ICD-11 criteria for PTSD and CPTSD are internationally relevant.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with aetiological factors associated with CPTSD, trauma experience in these settings is therefore likely to be protracted and impact both adults and children. For example, approximately 40% of adult participants in samples from northern Uganda were abducted in the 1980s as child soldiers, and civil conflict is ongoing in the region (Dokkedahl et al, 2015 ; Murphy et al, 2016 , 2018 ). In the case of South Africa, many people live in communities that are hubs of ongoing trauma, where violence is persistent and pervasive (Kaminer, Eagle, & Crawford-Browne, 2018 ), and many trauma survivors are children (Artz et al, 2016 ; Hsiao et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Findings related to the role of trauma history variables (e.g., type of trauma, its chronicity, and number of exposures to traumatic events) as risk factors for CPTSD have been somewhat mixed. Many studies have found a positive association between chronic childhood trauma exposure and a CPTSD symptom profile (Cloitre et al, 2013;Dokkedahl, Oboke, Ovuga, & Elklit, 2015;. The experience of cumulative childhood exposure to various types of interpersonal trauma (Hyland, Murphy, Shevlin, et al, 2017;Karatzias et al, 2017) has been more strongly associated with CPTSD than with PTSD symptom profiles.…”
Section: Introductionmentioning
confidence: 99%
“…Research supporting the validity of the ICD-11 CPTSD construct has, to date, been conducted among quite varied clinical and community samples who have been exposed to interpersonal violence. These include individuals who experienced both adult and childhood interpersonal violence (Cloitre et al, 2013;Karatzias et al, 2017), childhood sexual abuse victims Hyland, Shevlin, McNally, et al, 2016), survivors of institutional abuse (Knefel, Garvert, Cloitre, & Lueger-Schuster, 2015), a community sample of young adults exposed to interpersonal violence (Perkonigg et al, 2015), and a non-western (Ugandan) young adult sample exposed to civil war, including those abducted as children for soldiering (Dokkedahl et al, 2015;Murphy et al, 2016).…”
Section: Introductionmentioning
confidence: 99%